2021
DOI: 10.1002/14651858.cd013501.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Vegan dietary pattern for the primary and secondary prevention of cardiovascular diseases

Abstract: None of the trials reported on the occurrence of cardiovascular disease either in those with or without disease to begin with. Risk factors for cardiovascular disease were reported in the included studies. There was moderate-certainty evidence for some small reductions in lipid levels with the vegan diet compared to no or minimal intervention in people without disease, but also some very small changes in measures in the opposite direction for cardiovascular benefit. In people who already had cardiovascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 58 publications
3
8
1
Order By: Relevance
“…Despite the relatively short duration of restriction, the reduction in total and LDL cholesterol reported here (0.3 mmol/L) was larger or comparable to changes reported in meta-analyses of RCTs studying similar types of dietary interventions, including vegan diets that are three times longer in duration [6,7]. For example, in a meta-analysis of individuals at high risk of CVD, Rees et al report reductions of 0.24 mmol/L and 0.22 mmol/L for total and LDL cholesterol respectively, after at least 12 weeks of a vegan diet [7]. Similarly, Selinger et al [9] report a decrease of 0.48 mmol/L in LDL cholesterol in a meta-analysis of healthy individuals following a vegan diet for at least 12 weeks.…”
Section: Blood Lipidssupporting
confidence: 64%
See 2 more Smart Citations
“…Despite the relatively short duration of restriction, the reduction in total and LDL cholesterol reported here (0.3 mmol/L) was larger or comparable to changes reported in meta-analyses of RCTs studying similar types of dietary interventions, including vegan diets that are three times longer in duration [6,7]. For example, in a meta-analysis of individuals at high risk of CVD, Rees et al report reductions of 0.24 mmol/L and 0.22 mmol/L for total and LDL cholesterol respectively, after at least 12 weeks of a vegan diet [7]. Similarly, Selinger et al [9] report a decrease of 0.48 mmol/L in LDL cholesterol in a meta-analysis of healthy individuals following a vegan diet for at least 12 weeks.…”
Section: Blood Lipidssupporting
confidence: 64%
“…Given the impact of dietary intake on CVD risk, incorporating dietary information in CVD prediction models, in addition to the classical CVD risk factors, could improve robustness of patient classification and of CVD risk prediction. Despite the relatively short duration of restriction, the reduction in total and LDL cholesterol reported here (0.3 mmol/L) was larger or comparable to changes reported in meta-analyses of RCTs studying similar types of dietary interventions, including vegan diets that are three times longer in duration [7,8]. For example, in a meta-analysis of individuals at high risk of CVD, Rees et al…”
Section: Blood Lipidssupporting
confidence: 64%
See 1 more Smart Citation
“…Vegetarian and vegan diets are associated with better lipid profiles and a lower risk of ischemic heart diseases and diabetes ( 5 ). A recent Cochrane analysis found that vegan diets reduce the total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-c), though raise triglyceride (TG) and lower high-density lipoprotein cholesterol (HDL-c) slightly ( 6 ). Emerging evidence suggests that lipoprotein particles may be more predictive of cardiovascular outcomes than lipoprotein concentrations, and low-density lipoprotein particles (LDL-p) better account for residual risk after statin treatment than LDL-c ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In an 8-week trial in patients with coronary artery disease, C-reactive protein was lowered significantly by adherence to a vegan diet, when compared with the American Heart Association-recommended diet for coronary artery disease [5]. However, a recent Cochrane review concluded that at the moment there is insufficient information to draw conclusions about the effects of vegan dietary interventions on cardiovascular risk factors [6]. The high-fibre intake of these diets has been associated with fewer problems related to diet habits?…”
mentioning
confidence: 99%